Study on feeding and breeding management practices adopted by dairy farmers in Northern Telangana state (Indian Journal of Animal Production and Management, 2024)
Dairy farming plays an important role in social and economic livelihood of the farmers of Telangana state.  An investigation was carried out to examine feeding and breeding management practices adopted by the  farmers in Karimnagar, Kamareddy, Jagitial, and Peddapalli districts of Northern Telangana. Data was  collected from 240 dairy farmers from 24 villages of 8 mandals belonging to the above 4 newly formed  districts. A pretested semi-structured questionnaire in precise language was employed for collecting data  through interview and face to face discussion with the dairy farmers duly avoiding ambiguous, dichotomous  and non-variant items for proper interpretation. The data revealed that, majority of the farmers were practicing  grazing, group feeding and did not cultivate green fodder. Paddy straw was mostly used as dry fodder.  Majority of respondents fed homemade and compound cattle feed as concentrates to their milking animals  based on the milk production. Majority of respondents were offering soaked concentrates during milking.  Feeding mineral mixture and salt to their dairy animals was observed among majority farmers. Majority  farmers were able to recognize animals in heat by observing symptoms, followed artificial insemination  and bred their animals in mid-heat after heat detection. Most of the respondents preferred crossbreeding  and bred their animals after 2 to 3 months of calving. Majority of the respondents practiced pregnancy  diagnosis. Most of the respondents followed the treatment for anoestrus and repeat breeders. Only few  (4.17%) kept breeding records of their animals. It can be concluded that the majority of the respondents  in the study area had high knowledge on the oestrous cycle period and artificial insemination. Knowledge  levels of farmers about feeding and breeding management should be improved and frequent infertility  treatment camps should be organized at village and crossbred animals should be made available from  government farms at a reasonable price for sustainable dairying in villages.
Keywords: Breeding; Dairy farmer; Districts; Feeding; Management practices